PERSONALITY TRAITS AND WRITING–SPEAKING ACHIEVEMENT AMONG EFL TEACHER EDUCATION STUDENTS: A COMPARATIVE STUDY - Muhammad Irfan Arnis; Hesti Wahyuni (Jurnal Ilmiah Bina Bahasa, 2026)
Individual differences, particularly personality traits, are often assumed to influence learners’ productive language skills in the English as a Foreign Language (EFL) context. However, empirical evidence comparing their effects on both writing and speaking remains limited, particularly in Indonesian EFL teacher education programs. This study aimed to compare students’ writing and speaking achievement and to examine whether personality traits significantly differentiate these productive skills among English Education students at Sriwijaya University. A quantitative non-experimental comparative design was employed, involving 71 seventh-semester students. Data were collected using the Big Five Inventory (BFI), an essay-writing test, and a speaking performance test, and were analyzed using descriptive statistics, an independent-samples t-test, and a one-way ANOVA. The findings revealed no significant difference between students’ writing and speaking achievement (p > .05). Additionally, personality traits did not significantly influence either writing or speaking performance. These results indicate that productive language skills develop in a relatively balanced manner and are more strongly shaped by instructional and learning factors than by personality differences. This study provides empirical evidence that challenges deterministic views of personality in EFL learning and highlights the importance of inclusive instructional strategies to support productive skill development among diverse learners.